Folkcatholicism in central Mexico - Mendoza-Walker, Zoila (1988)
John Ingham's work brings a new perspective to the various studies on religious syncretism and on so-called "folk" or "popular" Catholicism in Latin America. Through a modern semiotic-structuralist approach, Ingham demonstrates how the symbols, themes, and patterns of medieval Spanish Catholicism have penetrated and taken root in the public and private spheres of what has come to be called "traditional culture" in central Mexico. The author shows how in Tlayacapan, the town where he carried out his extensive field research, popular Catholicism is an integral part of the most practical and intimate aspects of the daily life of the inhabitants.